Literasi Digital sebagai Tanggung Jawab Etis Pendidik Kristen - Andreas Kurniawan; Stefanus Dully; Tjutjun Setiawan (GLOSSAIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
This topic is written because, factually, the digital ethics of theology students tend not to be based on the principles of truth. This phenomenon demands that Christian educators not only master technology, but also develop ethical awareness in its use. This article aims to examine what digital literacy looks like as an ethical responsibility for Christian educators in the context of theological education. The method used is a descriptive-analytical approach that focuses on literature review (library research) to understand the relationship between faith, ethics, and digitalization. The research question is formulated as: How is the ethical responsibility of Christian educators manifested in the use of digital technology? The findings of this study reveal that digital literacy needs to be understood as the spiritual and ethical dimension of the Christian educator's calling. Theology, church, and Christian educational institution curricula need to collaborate to build a wise, faithful, and responsible digital culture within digital society. ABSTRAK Dasariah topik ini ditulis karena secara faktual, etika berdigital mahasiswa teologi cenderung tidak mendasarkan pada prinsip prinsip kebenaran. Fenomena ini menuntut pendidik Kristen tidak hanya menguasai teknologi, tetapi bagaimana para pendidik memiliki kesadaran etis dalam penggunaannya. Artikel ini bertujuan untuk mengkaji seperti apa literasi digital sebagai tanggung jawab etis pendidik Kristen dalam konteks pendidikan teologi. Metode yang digunakan adalah pendekatan deskriptif-analitis yang berfokus pada kajian literatur (library research untuk memahami hubungan terkait iman, etika, dan digitalisasi. Rumusan pertanyaan penelitian difokuskan pada bagaimana tanggung jawab etis pendidik Kristen diwujudkan dalam penggunaan teknologi digital? Temuan hasil kajian ini menngungkapkan bahwa literasi digital perlu dipahami sebagai dimensi spiritual dan etis dari panggilan pendidik Kristen. Kurikulum teologi, gereja, dan lembaga pendidikan Kristen perlu berkolaborasi membangun budaya digital yang bijak, beriman, dan bertanggung jawab di tengah masyarakat digital. Kata kunci: Literasi Digital, Etika Kristen, Pendidikan Teologi, Pendidik Kristen.